Phân tích đa thức thành nhân tử:
a. 2x2 - 3x - 2
b. 4x(x - 2) + 3(2 - x)
c. 27x3 + 8
d. x2 + 2x - y2 + 1
a. 2x2 - 3x - 2 = 2x2 - 4x + x - 2 = (2x2 - 4x) + (x - 2)
= 2x(x - 2) + (x - 2) = (x - 2)(2x + 1)
b. 4x(x - 2) + 3(2 - x) = 4x(x - 2) - (x - 2) = (x - 2)(4x - 1)
c. 27x3 + 8 = (3x)3 + 23 = (3x + 2)[(3x)2 - 2.3x + 22] = (3x + 2)(9x2 - 6x + 2)
d. x2 + 2x - y2 + 1 = (x2 + 2x + 1) - y2 = (x + 1)2 - y2
= (x + 1 - y)(x + 1 + y)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247